Involvement of NpdA, a Putative 2-Nitropropane Dioxygenase, in the T3SS Expression and Full Virulence in Ralstonia solanacearum OE1-1 - Zhang, Weiqi; Li, Jing; Tang, Yu; Chen, Kai; Shi, Xiaojun; Ohnishi, Kouhei; Zhang, Yong (Frontiers in Microbiology, 2017)
Previously, we isolated several genes that regulate the expression of the type III secretion system (T3SS) in Ralstonia solanacearum OE1-1strain. Here, we focused on the rsp0316, which encodes a putative 2-nitropropane dioxygenase (hereafter designated NpdA). The deletion of npdA substantially reduced the T3SS expression and virulence compared to that of the wild-type strain OE1-1, and the complemented npdA could completely restore its reduced T3SS expression and virulence to that of OE1-1 strain. The NpdA was highly conserved in R. solanacearum species and the NpdA-dependent expression of T3SS was not specific to OE1-1 strain, but NpdA was particularly required for the virulence of OE1-1 in host plants and the deletion of npdA did not affect the elicitation of hypersensitive response (HR) of R. solanacearum strains in tobacco leaves. The T3SS in R. solanacearum is directly controlled by the AraC-type transcriptional regulator HrpB and regulated by a complex regulation network. It was revealed here that NpdA affected the T3SS expression mediated HrpB but through some novel pathway. Moreover, NpdA was also important for the T3SS expression in planta but was not required for the growth of R. solanacearum in planta, indicating that the reduced virulence in OE1-1 might be due to the impaired T3SS expression in host plants. All these results genetically demonstrated that NpdA is a novel factor for the T3SS expression in R. solanacearum species, while it is particularly involved in the full virulence of OE1-1 in host plants.